Analisis Keterampilan Passing Futsal pada Siswa Ekstrakurikuler SMPN 3 Lembang: Tinjauan Gerak Kinematik - Septiani, Wulan; Darajat, Jajat; Gumilar, Agus (Jayabama: Jurnal Peminat Olahraga, 2024)
Passing skills in futsal are one of the basic techniques that are very important and determine the team's success in the game. Passing, or bait, is one of the main ways to transfer the ball from one player to another, ultimately building an attack or maintaining possession of the ball. Good passing skills allow a team to control the game, create space and open up scoring opportunities. The correct passing technique, be it short passes, long passes or crosses, must be mastered well by every player, because mistakes in passing can have fatal consequences, such as losing the ball which can be used by the opponent to score a goal. The aim of this research is to determine the passing ability of futsal players in extracurricular activities at SMPN 3 Lembang. The method used is descriptive research with a quantitative approach.